2022
DOI: 10.1097/md.0000000000032499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the regulatory mechanism of osteoporosis based on intestinal flora: A review

Abstract: Osteoporosis is 1 of the common diseases of bone metabolism in clinic. With the aging of the population in China, osteoporosis is becoming more and more serious, and it has become 1 of the major public health problems. However, traditional therapies, such as calcium therapy and estrogen therapy, can cause serious adverse effects and damage to the body when ingested over a long period of time. Therefore, there is an urgent need to explore alternative therapies with less side effects in clinical practice. Intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Whole-body vibration therapy is considered a promising physiotherapeutic measure to increase bone mass and density in age-related osteoporosis since it is effectively used in space medicine [194]. Among various risk factors of osteoporosis, gut microbiome disturbance affects osteoporosis development due to immune and endocrine mechanisms as well as via disruption of the gut-bone axis signaling [195]. So, the personalized use of pre-and probiotics and other therapies to restore the gut microbiome is highly recommended in therapeutic interventions in osteoporosis.…”
Section: Personalized Approaches In Osteoporosis Treatmentmentioning
confidence: 99%
“…Whole-body vibration therapy is considered a promising physiotherapeutic measure to increase bone mass and density in age-related osteoporosis since it is effectively used in space medicine [194]. Among various risk factors of osteoporosis, gut microbiome disturbance affects osteoporosis development due to immune and endocrine mechanisms as well as via disruption of the gut-bone axis signaling [195]. So, the personalized use of pre-and probiotics and other therapies to restore the gut microbiome is highly recommended in therapeutic interventions in osteoporosis.…”
Section: Personalized Approaches In Osteoporosis Treatmentmentioning
confidence: 99%
“…Recent studies on animal models have reported that the gut microbiota may also contribute to the regulation of bone metabolism, which ignited enthusiasm about the possibility of preventing bone loss by modulating the gut microbiota and even treating OP by mean of fecal microbiota transplantation (8). It is beyond the scope of this chapter to analyse the multiple mechanisms by which this may happen: the reader can find extensive reviews published in 2022 that examined the suggested connections between the gut microbiota and bone tissue (9)(10)(11)(12)(13)(14)(15)(16). Despite hundreds in vitro or animal studies illustrating an influence of the gut microbiota/microbioma on the skeleton, there are few studies involving humans.…”
Section: The Relationship Between Gut Microbiota and Bone: Do We Have...mentioning
confidence: 99%